Besaran Limbah Padat Industri Kelapa Sawit Di PT. Perkebunan Nusantara V (Persero) Sei Galuh Kabupaten Kampar - Yulya Yulya; Aryo Sasmita; Shinta Elystia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
PT. Perkebunan Nusantara V (Persero) Sei Galuh is the palm oil industry that will result in the emission of particulate matter. One of the causes of the emergence of the particulate is boiler and incinerator. Boiler and incinerator is burning solid waste resulting from a processing oil palm activities, so it is necessary to know the pattern of distribution of the emissions from oil palm industry activities that are in PT. Perkebunan Nusantara V (Persero) Sei Galuh. This research is descriptive research method using Gaussian dispersion with a SCREEN View. The parameter is the number of solid waste oil palm. Data presented in the form tables. The amount of palm oil solid waste PT. Perkebunan Nusantara V (Persero) Sei Galuh which was burned in a boiler of 20,299,668 kg. While the amount of palm oil solid waste PT. Perkebunan Nusantara V (Persero) Sei Galuh which was burnt on an incinerator of 22,206,015 kg.Keywords: particulate, boilers, incinerators.